CONSUMER PREFERENCES TOWARD PINDANG CUISINE IN PALEMBANG - Ibrahim, Muhammad Febriansyah; Saputra, Agusriansyah; Novriana, Zetira; Dermawan, Alvindo; Nasution, Erwin Efendi; Akbar, M. Farandika (Journal of Business Studies and Management Review, 2026)
This study aimed to identify the most important attributes of pindang cuisine based on consumer preferences in Palembang. This study employed a quantitative descriptive approach to examine the characteristics and responses of consumers regarding the purchase of Pindang. The data used in this study consisted of primary data collected through an online questionnaire distributed by Google Forms. The questionnaire was distributed between December 2025 to February 2026. The research instrument comprised a structured questionnaire divided into three main sections: respondent profile, pindang purchase behavior, and consumer preference attributes. Consumer preferences for each pindang attribute were determined using a weighted scoring method based on a Likert-scale score. This study involved 356 respondents selected through purposive sampling based on predefined inclusion criteria. Eligible participants were individuals who had purchased or consumed pindang at a pindang restaurant in Palembang within the six months preceding the survey. The sampling technique used in this study was non-probability sampling through an online survey. The data obtained were then analyzed descriptively by calculating the frequency, percentage, and average values of the respondents’ answers. The result showed that RM. PMR achieved the highest consumer preference score among pindang restaurants in Palembang. This preference is likely associated with its high popularity and strong appeal among consumers. Fish was the main ingredient in pindang at 60.4%, with river catfish (Pangasius pangasius) being the most dominant species at 48.9%. The fish body was the most preferred part because it has thick flesh, a uniform texture, is easy to eat, and has a richer flavor. The health aspect received the highest perception score of 4.92, while taste was the most dominant sensory attribute with a score of 4.92. Additionally, the product factor received the highest importance score with a score of 4.80, indicating that product quality was the primary determinant of consumer evaluations and satisfaction